About descent property for extragradient algorithm - Коваленко, О. Ю.; Гончаренко, Ю. В. (Київський національний університет імені Тараса Шевченка, 2025)
A new result on the descent property of the extragradient algorithm is proved, and for unconstrained problems, an estimate of the algorithm speed in terms of natural residuals is obtained under weaker conditions than known ones.

Доведено новий результат щодо властивостi спуску екстраградiєнтного алгоритму, а для задач без обмежень отримано оцiнку швидкостi екстраградiєнтного алгоритму в термiнах природної нев’язки за слабших умов, нiж вiдомi.
Про властивiсть спуску для екстраградiєнтного алгоритму
Keywords: variational inequality; operator equation; monotone operator; extragradient algorithm; rate of convergence; варiацiйна нерiвнiсть; операторне рiвняння; монотонний оператор; екстраградiєнтний алгоритм; швидкiсть збiжностi